Application of blockchain technology in the management of waqf institutions: concepts, challenges and recommendations - Salleh, Norsaremah; Kassim, Salina; Muhammad, Niaz Makhdum; Mohd Yusoff, Syarah Syahira; Mahadi, Nur Farhah; Md Ariffin, Kartina (IEEE, 2023)
Existing studies on performance aspects of waqf institutions have mainly focused on quantitative aspects, including financial ratios, with no inclusion of other alternative analysis tools such as qualitative measurement. To the best of our knowledge, research effort in this area has been lacking. Moreover, there is a literature gap in the adoption of modern technology such as blockchain technology in the management of the waqf entities. This is undoubtedly the missing impetus to the growth and effciency of waqf sector, realising the high degree of accuracy, accountability and reliability it demands. This study aims to explore into the feasibility of incorporating the blockchain technology to be applied in the performance measurement system that is credible and reliable for waqf institutions in Malaysia. Three experts working in Malaysian Fintech companies were interviewed, and thematic analysis approach was used for interpreting the data. This study delves into the understanding of how the blockchain technology leads to a performance measurement system that is credible and reliable for waqf institutions in Malaysia. As found in this study, there is a necessity for using effective blockchain-based performance measurement systems for Waqf institutions once the knowledge and maturity are acquired, which will contribute towards developing a more comprehensive waqf sector. It is expected that the outcomes of this study will contribute towards enriching the literature on measuring waqf organization performance.